(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
These days the turbocharging system is assuming an essential part in enhancing car engines performance and diminishing fuel utilization and the fumes emanations, in spark-ignition and compression ignition engines. The performance of a radial turbine for the turbocharger device is heavily affected by the flow dynamics in a radial impeller. Furthermore, modification and improvement of a radial turbine impeller is a challenging task for turbomachinery engineers. Hence, this study aimed to further computational fluid dynamic analyses of a radial turbine stage performance .The design characteristics of a radial turbine stage, was used to simulate the flow by using independent packages of ANSYS CFX. The comparative study of a three dimensional flow simulation will give a more reasonable results of the turbine stage flow behavior and computational fluid dynamic simulation can give a more detailed result and reveal unexpected flow behavior like separation and vortexes.The results showed that the fluid flow dynamics within a turbine stage has indicated a noticeable performance characteristics. Obviously, it was observed that the pressure ratio and volume flow rate and efficiency were predicted numerically. Overall numerical results obtained from computational fluid dynamic simulations could produce a highly reliable for estimation on the performance a radial turbine of turbocharger.